(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2018)
For this study, 148 students were recruited, and they consisted of two experimental groups and one control group. Both experimental groups were instructed in the development of conceptual maps using the CmapTools software, while the students in the control group freely chose which study strategies they would use to acquire the knowledge that would be evaluated. The difference between the two experimental groups was that one of the experimental groups followed the guidelines of a cooperative activity, developing a conceptual map in work teams (4 students to each team) using CmapCloud, while in the other experimental group, each student developed the contents of a conceptual map in CmapTools on an individual level. The objective was to detect whether there would be any statistically significant differences between the three groups at the level of academic performance. For this purpose, the same sample was tested by means of the same type of knowledge acquisition test. The data obtained reveal that the scores are higher in the experimental groups than in the control group, and in turn, the experimental group that included cooperative work obtained a better level of performance than the experimental group that worked at the individual level. Therefore, we conclude that simple modifications in the pedagogical strategy (introducing an effective learning strategy and cooperative work), would significantly improve the teaching-learning process and, consequently, would significantly improve the average performance of the students.